AVALIAÇÃO DE PASTAS DE CIMENTO PORTLAND FORMULADAS COM CP II F E CINZA DE CARVÃO MINERAL VISANDO A CIMENTAÇÃO DE POÇOS DE PETRÓLEO - Cirino, Miguel Adriano Gonçalves; Cabral, Antonio Eduardo Bezerra (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
Portland cement slurries formulated with cements commonly used in civil construction don’t fully meet the normative requirements of the API (American Petroleum Institute), especially about the mechanical properties, due to the composition characteristics and properties required for oil wells cementing. Due to these characteristics, in Brazil, specific Portland cements are used for oil wells, such as CPP Class G and CPP Especial Class. The research sought to evaluate a reliable alternative of cement slurries formulated with CPII F cement, with great availability in the market, with partial substitution of the cement by coal burning ashes to 5% and 10%, chosed for modifying the microstructure and the resistance of the slurries. The ash comes from the Pecém-CE thermoelectric plants, which represents an environmental liability due to the provision in patios of accumulation of this industrial waste. Initially, the chemical and microstructural cement and the ashes were characterized as the pozzolanic activity. Subsequently, the technological tests required by NBR 9831/2006 and API ASPEC / 2010 were carried out for the cementation of oil wells. It is concluded that the formulated slurries presented the possibility of cementing applications of shallow wells.